Congestive Heart Failure in Diphtheric Myocarditis - A. M. Prasodo; M. Narendra; A. Joernil; Wahjoenarso Wahjoenarso; F. Kaspan (Indonesian Pediatric Society, 1976)
The picture of congestive heart failure in diphtheric myocarditis was mainly determined by poor general condition, hepatic enlargement + epigastric pain, dyspnea. Basal rales and peripheral edema were not observed. Cardiomegaly on X-ray examination supported the diagnosis. Congestive heart failure as a complication of diphtheric myocarditis occurred in 31.2% - 52% of cases with severe ECG changes and only in 5% of cases with ST depression or T wave changes. Of 29 cases with congestive heart failure only 3 survived. Apparently good results of digitalis treatment were obtained when only gallop rhythm, as an early sign of heart failure, was found. Extensive myocardial damage by diphtheria toxin may explain why no beneficial effect of digitalis treatment was obtained. Prophylactic digitalization before signs of congestive heart failure appeared, as suggested by several authors; was not performed in this study.